2020
DOI: 10.1017/s2040174420000719
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal parenteral nutrition affects the metabolic flow of glucose in newborn and adult male Hartley guinea pigs’ liver

Abstract: Extremely premature birth is associated with a permanent disruption of energy metabolism. The underlying mechanisms are poorly understood. The oxidative stress induced by parenteral nutrition (PN) during the first week of life is suspected to reprogram energy metabolism in the liver. Full-term male Hartley guinea pigs (to isolate PN from prematurity) receiving PN enriched or not with glutathione (to isolate PN effects from PN-induced oxidative stress effects) or an Oral Nutrition (ON) during the first week of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 60 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…NADPH concentrations for both assays were extrapolated from a slope calculated with increasing NADPH quantities, ranging from 0 to 1 mmol. Glucokinase (GCK) activity was assayed as described previously [16]. Briefly, liver was homogenized in 2 volumes of buffer (100 mM Tris-HCl pH 7.5, 5 mM EDTA-Na 2 , 5 mM MgCl 2 , 150 mM KCl, and 50µM 2-mercaptoethanol) and centrifuged at 1400× g/20 min/4 • C. Glucokinase activity was determined by increasing the absorbance at 340 nm in a reaction containing 0.5 mM ATP, 0.4 mM NADP, 0.067 U/mL G6PDH, and 0.5 mM or 100 mM of glucose added to the buffer (100 mM Tris-HCl pH 7.5, 5 mM MgCl 2 ) for 1 h/30 • C. Glucokinase activity was calculated by the subtraction of the activity measured with 0.5 mM glucose (hexokinase), from the one measured at 100 mM (hexokinase + glucokinase).…”
Section: Animal Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…NADPH concentrations for both assays were extrapolated from a slope calculated with increasing NADPH quantities, ranging from 0 to 1 mmol. Glucokinase (GCK) activity was assayed as described previously [16]. Briefly, liver was homogenized in 2 volumes of buffer (100 mM Tris-HCl pH 7.5, 5 mM EDTA-Na 2 , 5 mM MgCl 2 , 150 mM KCl, and 50µM 2-mercaptoethanol) and centrifuged at 1400× g/20 min/4 • C. Glucokinase activity was determined by increasing the absorbance at 340 nm in a reaction containing 0.5 mM ATP, 0.4 mM NADP, 0.067 U/mL G6PDH, and 0.5 mM or 100 mM of glucose added to the buffer (100 mM Tris-HCl pH 7.5, 5 mM MgCl 2 ) for 1 h/30 • C. Glucokinase activity was calculated by the subtraction of the activity measured with 0.5 mM glucose (hexokinase), from the one measured at 100 mM (hexokinase + glucokinase).…”
Section: Animal Modelmentioning
confidence: 99%
“…We have previously shown that guinea pigs submitted to PN during the first days of life develop glucose intolerance, are less physically active [17], and have altered levels of key energy metabolism enzymes in the liver at adult life [16]. On this same model of PN-induced oxidative stress, most of early life impacts of PN are due to peroxides, but many long-term effects of PN remain after the effect of early peroxides is prevented.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations